A Bivalent Anthrax–Plague Vaccine That Can Protect against Two Tier-1 Bioterror Pathogens, Bacillus anthracis and Yersinia pestis - Tao, Pan; Mahalingam, Marthandan; Zhu, Jingen; Moayeri, Mahtab; Kirtley, Michelle L.; Fitts, Eric C.; Andersson, Jourdan A.; Lawrence, William S.; Leppla, Stephen H.; Chopra, Ashok K.; Rao, Venigalla B. (Frontiers in Immunology, 2017)
Bioterrorism remains as one of the biggest challenges to global security and public health. Since the deadly anthrax attacks of 2001 in the United States, Bacillus anthracis and Yersinia pestis, the causative agents of anthrax and plague, respectively, gained notoriety and were listed by the CDC as Tier-1 biothreat agents. Currently, there is no FDA-approved vaccine against either of these threats for mass vaccination to protect general public, let alone a bivalent vaccine. Here, we report the development of a single recombinant vaccine, a triple antigen consisting of all three target antigens, F1 and V from Y. pestis and PA from B. anthracis, in a structurally stable context. Properly folded and soluble, the triple antigen retained the functional and immunogenicity properties of all three antigens. Remarkably, two doses of this immunogen adjuvanted with Alhydrogel elicited robust antibody responses in mice, rats, and rabbits, and conferred complete protection against inhalational anthrax and pneumonic plague. No significant antigenic interference was observed. Further, we report, for the first time, complete protection of animals against simultaneous challenge with both the Tier-1 bioterror agents, demonstrating that a single biodefense vaccine can protect against a bioterror attack with weaponized B. anthracis and/or Y. pestis. This bivalent anthrax-plague vaccine is therefore a strong candidate for stockpiling, after demonstration of its safety and immunogenicity in human clinical trials, as part of national preparedness against two of the deadliest bioterror threats.